The indoor air quality and the occurrence of sick building syndrome among employees in the central surgery building of hospital X, Bandung - Hefnita, Hefnita; Budiyono, Budiyono; Suhartono, Suhartono (Malahayati International Journal of Nursing and Health Science, 2025)
Background: The prevalence of SBS (Sick Building Syndrome) among employees working in hospitals ranges from 21% to 80%, which is higher compared to other places. SBS has become an issue due to poor indoor air quality, including at Hospital X in Bandung. Purpose: To analyze the relationship between indoor air quality and the incidence of Sick Building Syndrome among workers in the Central Surgery Building of Hospital X, Bandung. Method: An analytical observational study with a cross-sectional design. The study population consisted of 105 permanent employees of the Central Surgery Unit. A sample of 91 workers was selected using random sampling. Inclusion criteria were permanent employment and working >7 hours a day, while exclusion criteria included employees on leave, sick, or unavailable. Data were collected through observation using instruments such as a thermohygrometer to measure temperature and humidity, a lux meter for lighting, a sound level meter for noise, and an anemometer for ACH (Air Changes per Hour), following the standards of the Ministry of Health Regulation No. 2 of 2023. Additionally, interviews were conducted using a questionnaire containing questions about SBS symptoms to gather data on the occurrence of SBS. Data analysis used Chi-square and logistic regression at a 95% confidence level and an alpha of 0.05. Results: The study results indicated that the indoor air quality did not meet the required standards: temperature (77.3%), humidity (86.4%), lighting (63.6%), noise (0%), bacterial count (63.3%), fungal count (77.3%), and ACH (63.3%). There was a significant relationship between temperature, humidity, and ACH with the occurrence of SBS (p=0.001; p=0.003; p=0.031). However, there was no significant relationship between lighting, bacterial count, and fungal count with SBS (p=0.181; p=0.264, p=0.066). Conclusion: Temperature, humidity, and ACH are variables that are associated with the occurrence of SBS.